On the Role of Focus-Sensitivity for a Typology of Presupposition Triggers. (10th October 2022) - Göbel, Alexander
Abstract: This paper presents two experiments comparing presupposition triggers that differ with respect to Focus-sensitivity. The hypothesis was that Focus-sensitive (+focus ) triggers require a linguistic antecedent in the discourse model, whereas presuppositions of triggers lacking Focus-sensitivity (–focus ) are satisfied as entailments of the Common Ground. Each experiment tested a distinct prediction of this hypothesis, namely (i) being subject to salience, operationalized relative to the QUD, and (ii) global accommodation difficulty. Experiment 1 compared too as a +focus trigger and again as a –focus trigger in short dialogues and manipulated the presence or absence of material intervening between the target sentence containing the trigger and the utterance satisfying its presupposition. Intervening material led to a decrease in ratings as well as longer full sentence reading times of the target sentence for too but not again, in line with the prediction. Experiment 2 compared four trigger pairs that differed in Focus-sensitivity relative to presuppositionless control in a rating study in contexts that did not explicitly satisfy their presupposition. As predicted, +focus triggers showed a larger decrease in ratings than –focus triggers. The picture that emerges from these results is that the same kind of meaning - presuppositions - can be grounded in different aspects of the context in relation to an independent property of the trigger - Focus-sensitivity - which directly affects the discourse behavior of a trigger. The paper concludes with a discussion of some implications of the findings for linguistic theory, in particular anaphoricity.